Active components of essential oils as acaricides against Dermanyssus gallinae - Radsetoulalova, I; Hubert, J; Hampel, D; Lichovnikova, M (British poultry science, 2020)
1. The aim was to evaluate the acaricidal effects of pure active components of essential oils against poultry red mite (Dermanyssus gallinae) as an alternative to chemical acaricides (organophosphates and pyrethroids).2. The toxicities of five pure active components of essential oils (eugenol from clove bud, eucalyptol from rosemary, limonene from citrus fruits, linalool from lavender and cinnamaldehyde from cinnamon) were tested on D. gallinae females in an impregnated paper assay.3. The active substances were dissolved in water and Tween 20 and applied at concentrations ranging from 0.002 to 0.06 µl/cm2. Toxicity was expressed as a lethal dose (LD50 or LD90).4. The highest mortality was observed with eugenol. The LD90 was estimated to be 5.1 µg/cm2 for this substance, followed by cinnamaldehyde, the LD90 of which was estimated to be 11.0 µg/cm2. Limonene and eucalyptol were generally less effective in controlling D. gallinae.
Keywords: roztoči; Cinnamaldehyde; Syzygium; oleje prchavé; Chickens; limonene; Female; Mites; zvířata; eucalyptol; akaricidy; eugenol; Poultry red mite elimination; kur domácí; ženské pohlaví; Acaricides; Oils, Volatile; Animals; linalool